Race and in-hospital mortality after spontaneous intracerebral hemorrhage in the Stroke Belt: Secondary analysis of a case–control study. Issue 1 (16th March 2021) - Hilton, Logan D.; Lyerly, Michael J.; Gropen, Toby I.
Abstract: Background and Purpose: Intracerebral hemorrhage (ICH) accounts for around 10% of stroke, but carries 50% of stroke mortality. ICH characteristics and prognostic factors specific to the Stroke Belt are not well defined by race. Methods: Records of patients admitted to the University of Alabama Hospital with ICH from 2017 to 2019 were reviewed. We examined the association of demographics; clinical and radiographic features including stroke severity, hematoma volume, and ICH score; and transfer status with in-hospital mortality and discharge functional status for a biracial population including Black and White patients. Independent predictors of in-hospital mortality and functional outcome were examined using logistic regression. Results: Among the 275 ICH cases included in this biracial analysis, Black patients ( n = 114) compared to White patients ( n = 161) were younger (60.6 vs. 71.4 years, P < 0.0001), more often urban (81% vs. 64%, P < 0.01), more likely to have a history of hypertension (87% vs. 71%, P < 0.01), less often transferred (44% vs. 74%, P < 0.01), and had smaller median initial hematoma volumes (9.1 vs. 12.6 mL, P = 0.041). On multivariable analysis, Glasgow Coma Scale (GCS) for White patients (OR 13.0, P < 0.0001), hyperlipidemia for Black patients (OR 13.9, P = 0.019), and ICH volume for either race (Black patients: OR 1.05, P = 0.03 and White patients: OR 1.04, P < 0.01) were independent predictors of in-hospital mortality. Conclusions: Hypertension is more prevalent among Black ICH patients in the Stroke Belt. The addition of hyperlipidemia to the ICH score model improved the prediction of mortality for Black ICH patients. No differences in in-hospital mortality or poor functional outcome were observed by race.